2016
DOI: 10.1177/0969733015583926
|View full text |Cite
|
Sign up to set email alerts
|

The moral courage of nursing students who complete advance directives with homeless persons

Abstract: Our results cannot be generalized, but portions of our approach are likely to be transferable to similar social contexts. For example, because homeless persons are misunderstood and marginalized throughout the United States, our design for training nursing students to provide this service is also likely to be useful across the United States. Internationally, however, it is not yet known whether our participants' fears and the challenge they faced are also experienced by those who assist homeless persons or mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 26 publications
0
38
0
6
Order By: Relevance
“…Study findings revealed that students' preceding fears included acting inappropriate in front of the patient and fear of discussing dying and death with a homeless person. 10 However, it was found that after interaction with homeless persons, none of the preconceived fears occurred; rather, they concluded students needed more courage in anticipation of such events. 10 Having moral courage as a nurse is a valuable characteristic, not only for patient safety but also because of its recently established correspondence with preventing moral distress.…”
Section: Courage In Nursingmentioning
confidence: 97%
See 3 more Smart Citations
“…Study findings revealed that students' preceding fears included acting inappropriate in front of the patient and fear of discussing dying and death with a homeless person. 10 However, it was found that after interaction with homeless persons, none of the preconceived fears occurred; rather, they concluded students needed more courage in anticipation of such events. 10 Having moral courage as a nurse is a valuable characteristic, not only for patient safety but also because of its recently established correspondence with preventing moral distress.…”
Section: Courage In Nursingmentioning
confidence: 97%
“…10 However, it was found that after interaction with homeless persons, none of the preconceived fears occurred; rather, they concluded students needed more courage in anticipation of such events. 10 Having moral courage as a nurse is a valuable characteristic, not only for patient safety but also because of its recently established correspondence with preventing moral distress. 11 Moral distress occurs when a person knows the right action to take, but cannot take the correct action due to constraints (internal and external).…”
Section: Courage In Nursingmentioning
confidence: 97%
See 2 more Smart Citations
“…In previous research, nursing students described anxiety around discussing death and dying with this group, yet completion of the advance directive with this group was rated as less challenging than anticipated. 47 People experiencing homelessness have been willing to talk about end-of-life care wishes 24 and complete advance directives 48 in previous research, particularly when one to one support is provided. 19 35–37 In this research, avoidance and denial of these issues was apparent.…”
Section: Discussionmentioning
confidence: 99%